O impacto da nova legislação (lei Nº 12.815/13) no crescimento do setor portuário brasileiro: uma análise abordando a dinâmica de sistemas - Leite, Daniel Farinelli (2019)
The new regulatory framework for the Brazilian port sector (Law 12.815 / 13) brought a new form of administrative management with the objective of increasing port efficiency through affordable costs and increased competition between ports and terminals. The objective of this research was to carry out a quantitative approach in a systemic conceptual model to analyze whether this new regulatory framework has brought or is bringing growth to the sector. For this analysis, the Dynamics of Systems technique was used by means of a computational simulation approach to generate analytical data and compare them with the actual results of the sector, in addition to designing possible scenarios. To achieve these objectives, data were analyzed from 200 Brazilian ports, of which 171 were private ports and 29 public ports, from 2014 to 2017. The computational model was validated using the technique of comparing the data projected by the computational model with the actual data of the sector, which incurred an average error of | -0.63% |. For the analysis, three scenarios were projected: optimistic, conservative and pessimistic, with average annual growth of 4%, 2.2% and 0.5%, respectively. The main indicator of growth of the Brazilian port sector was the total cargo movement of the national ports. After the scenario analysis, it was concluded that the promulgation of the new regulatory framework of the Brazilian port sector, has brought and will continue to bring an exponential growth to the sector, thus reaching the main objective of the study.